Perbuatan Berlanjut Sebagai Dasar Pemberatan Pidana Terhadap Tindak Pidana Persetubuhan Anak: (Analisis Putusan Nomor: 413/Pid.Sus/2020/PN.Dum) - Septinus Halawa (Yayasan Literasi Sains Indonesia, 2023)
The application of the law against perpetrators of child sexual relations deserves serious attention. Law enforcers in processing and making decisions must be absolutely sure that the decision taken will be a strong basis for providing legal protection to children as victims. The formulation of the problem in this research is how to carry out the criminal aggravation in the crime of sexual intercourse with a child which is carried out continuously, how the criminal elements are applied in the ongoing crime of child sexual intercourse in Decision Number: 413/Pid.Sus/2020/PN.Dum, and how analysis of the judge's considerations in deciding the crime of continued child sexual intercourse based on Decision Number: 413/Pid.Sus/2020/PN.Dum. The research method used in this research is normative juridical research, which is supported by primary data sources and secondary data, and qualitative analysis is carried out. Article 473 paragraph (4) of Law Number 1 of 2023 regulates criminal penalties for the crime of sexual intercourse with a child which is carried out continuously. Perpetrators who force children to have sexual intercourse with violence or threats of violence can be subject to imprisonment for a minimum of 3 years and a maximum of 15 years. The judge cannot impose sanctions under 5 years in prison in accordance with applicable legal provisions. All these considerations aim to create a sense of justice in society.